Acting : onstage and off - Barton, Robert, 1945- (Australia ; United States : Wadsworth/Cengage Learning, 2012)
'Demonstrating how offstage performance can be effectively adapted for the theatre, as well as how onstage training can be applied toward leading a full life outside the theatre,'Acting: Onstage and Off' is a humorous yet informative book that discusses the interplay between life on and off the stage. You'll learn everything from the phases of actor training to body-relaxation techniques.'--Publisher description.
Includes bibliographical references and index.
Keywords: Acting; Method acting